Unintentional ingestion of black henbane: two case reports. Issue 1 (1st January 2017) - Shams, Tahireh Ashley; Gosselin, Sophie; Chuang, Ryan
ABSTRACT: Black henbane (Hyoscyamus niger) is a member of the nightshade family and an invasive species that grows world-wide, including in Canada. Black henbane is toxic due to its tropane alkaloid contents: hyoscyamine, scopolamine (hyoscine), and atropine. We present two cases of unintentional, acute henbane poisoning. A 65-year-old woman and her 71-year-old husband presented to the emergency department with tachycardia, confusion, hallucinations, and urinary retention after eating a plant thought to be a parsnip from their garden, later identified by family as black henbane. During admission, the woman developed an asymptomatic new left bundle branch block with no other signs of ischemia. Both patients were managed supportively; their toxidromes resolved within 36-48 hours. These cases illustrate the rapid antimuscarinic effects associated with black henbane poisoning. This is the first report describing a new left bundle branch block in the context of black henbane poisoning. However, no published reports of sodium channel activity with any of the constituents was found. Increased public information is needed to educate individuals on the recognition of these mimic plants, as well as the dangers of ingestion, given their ubiquity in private gardens.